Aluminum alloy forgings and manufacturing method thereof
By controlling the element content in Al-Mg-Si alloy and adopting a specific heat treatment process, the problem of coarse grain generation in the alloy during forging and heat treatment is solved, and the excellent mechanical properties of aluminum alloy forged products at room temperature and the effect of difficulty in generating back-crystallised grains is achieved.
Patent Information
- Application Number
- JP2020206752
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-12-14
AI Technical Summary
High-strength Al-Mg-Si alloys are prone to coarse grains during forging and heat treatment, resulting in poor mechanical properties. Although the addition of Zr can prevent back crystallization, it will lead to weakening of particle size refining effect, increasing internal defects of forged products and contamination in the furnace.
Aluminum alloy forging products that are difficult to generate back-crystallised grains are prepared by controlling the element content range in the alloy and adopting specific heat treatment processes including melt formation, casting, homogenous heat treatment, forging, dissolution heat treatment, rapid cooling and weathering.
It realizes that aluminum alloy forged products have excellent mechanical properties at room temperature, reduces the generation of re-crystallized grains, and improves the strength and weather resistance of the products.
Smart Images

Figure 0007647085000003 
Figure 0007647085000001 
Figure 0007647085000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an Al-Mg-Si aluminum alloy forging having excellent mechanical properties at room temperature, and a method for producing the same. [Background technology]
[0002] In recent years, aluminum alloys have been widely used as structural components for various products, taking advantage of their light weight. For example, high-tensile steel has been used for the suspension and bumper parts of automobiles, but in recent years, high-strength aluminum alloy materials have been used. For automobile parts, such as suspension parts, iron-based materials have been used exclusively, but they are increasingly being replaced by aluminum or aluminum alloy materials, mainly for the purpose of reducing weight.
[0003] These automobile parts require excellent corrosion resistance, high strength, and excellent workability, so Al-Mg-Si alloys, especially A6061, are widely used as aluminum alloy materials. In order to improve the strength of these automobile parts, they are manufactured by forging, which is a type of plastic processing, using aluminum alloy materials as the processing material.
[0004] Recently, due to the need to reduce costs, suspension parts have begun to be put into practical use in which cast parts are used as the raw material without extrusion, and then subjected to T6 treatment. In order to further reduce weight, development of high-strength alloys to replace the conventional A6061 is underway (see Patent Documents 1 to 3 below). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 5-59477 [Patent Document 2] Japanese Patent Application Publication No. 5-247574 [Patent Document 3] Japanese Patent Application Publication No. 6-256880 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the above-mentioned high-strength Al-Mg-Si alloys have a problem in that the processed structure recrystallizes during the forging and heat treatment processes, resulting in the generation of coarse crystal grains, making it impossible to obtain sufficient strength. Therefore, some alloys contain Zr to prevent recrystallization in order to prevent the generation of coarse recrystallized grains (for example, Patent Documents 1 and 2).
[0007] Although the addition of Zr is effective in preventing recrystallization, it has the following problems.
[0008] (1) The addition of Zr weakens the effect of refining the crystal grains of the Al-Ti-B alloy, coarsening the crystal grains of the ingot itself, leading to a decrease in the strength of the processed product (forged product) after plastic processing.
[0009] (2) The effect of refining the crystal grains of the ingot itself is weakened, so that the ingot is more likely to crack, the number of internal defects increases, and the yield decreases.
[0010] (3) Zr forms compounds with Al-Ti-B alloys. These compounds accumulate at the bottom of the furnace in which the molten alloy is stored, contaminating the furnace. In addition, these compounds also crystallize out as coarse particles in the produced ingots, reducing their strength.
[0011] Thus, although the addition of Zr is effective in preventing recrystallization, it is difficult to maintain the stability of strength.
[0012] The present invention has been made in consideration of the above technical background, and has an object to provide an aluminum alloy forging that has excellent mechanical properties at room temperature and is less susceptible to the generation of recrystallized grains, and a manufacturing method thereof. [Means for solving the problem]
[0013] In order to achieve the above object, the present invention provides the following means.
[0014] [1] An aluminum alloy forging containing 0.15% by mass to 1.0% by mass of Cu, 0.6% by mass to 1.3% by mass of Mg, 0.60% by mass to 1.45% by mass of Si, 0.03% by mass to 1.0% by mass of Mn, 0.2% by mass to 0.4% by mass of Fe, 0.03% by mass to 0.4% by mass of Cr, 0.012% by mass to 0.035% by mass of Ti, 0.0001% by mass to 0.03% by mass of B, a Zn content of 0.25% by mass or less, a Zr content of 0.05% by mass or less, and the balance being Al and unavoidable impurities, The intensity of the diffraction peak of the AlFeMnSi phase in the X-ray diffraction pattern obtained by X-ray diffraction measurement of the cross section of the forged product is defined as "Q 1 (cps), and the intensity of the diffraction peak of the (200) plane of the Al phase is "Q 2 " (cps), Q 1 / Q 2 The value is 8 x 10 -3 1. An aluminum alloy forging product, characterized in that:
[0015] [2] A method for producing an aluminum alloy forging according to the preceding paragraph 1, comprising the steps of: a molten metal forming step for obtaining a molten metal; a casting step of obtaining a casting by casting the molten metal obtained in the molten metal forming step; a homogenization heat treatment step in which homogenization heat treatment is performed on the casting obtained in the casting step; A forging process for obtaining a forged product by forging the cast product after the homogenization heat treatment process; a solution treatment step of subjecting the forged product obtained in the forging step to a solution treatment; a quenching treatment step of quenching after the solution treatment step; and an aging treatment step of subjecting the forged product after the quenching treatment step to aging treatment.
[0016] [3] The homogenization heat treatment step is a homogenization heat treatment step in which the casting obtained in the casting step is held at a temperature of 370°C to 560°C for 4 hours to 10 hours, The forging process is a process of forging the casting after the homogenization heat treatment process at a heating temperature of 450°C to 560°C. The solution treatment step is a step of heating the forged product obtained in the forging step from 20°C to 500°C at a heating rate of 5.0°C / min or more, and then holding the product at 530°C to 560°C for 0.3 hours to 3 hours. In the quenching treatment process, the entire surface of the forged product is brought into contact with quenching water within 5 to 60 seconds after the solution treatment process, and quenching is performed in a water tank for more than 5 minutes but not exceeding 40 minutes, 3. The method for producing an aluminum alloy forged product according to item 2 above, wherein the aging treatment step comprises heating the forged product after the quenching treatment step at a temperature of 180°C to 220°C for 0.5 hours to 1.5 hours to perform aging treatment. Effect of the Invention
[0017] According to the invention of [1], the content of each element is set within a predetermined range, and Q 1 / Q 2 The value is 8 x 10 -3 By satisfying the above condition, it is possible to provide an aluminum alloy forging having excellent mechanical properties at room temperature and in which recrystallized grains are unlikely to occur.
[0018] According to the invention of [2], by including a molten metal forming process, a casting process, a homogenization heat treatment process, a forging process, a solution treatment process, a quenching treatment process and an aging treatment process, it is possible to manufacture an aluminum alloy forging having excellent mechanical properties at room temperature and being resistant to recrystallization grains.
[0019] According to the invention [3], by setting the processing conditions in each processing step within a predetermined range, it is possible to produce an aluminum alloy forging that has even better mechanical properties at room temperature and is less susceptible to the generation of recrystallized grains. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a perspective view showing an aluminum alloy forging obtained by the manufacturing method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The aluminum alloy forgings and the method for producing the aluminum alloy forgings of the present invention will now be described.
[0022] It should be noted that the embodiments described below are merely examples, and the present invention is not limited to these exemplified embodiments, but may be modified as appropriate within the scope of the technical concept of the present invention.
[0023] The aluminum alloy forged product 1 of this embodiment contains 0.15 mass% to 1.0 mass% Cu, 0.6 mass% to 1.3 mass% Mg, 0.60 mass% to 1.45 mass% Si, 0.03 mass% to 1.0 mass% Mn, 0.2 mass% to 0.4 mass% Fe, 0.03 mass% to 0.4 mass% Cr, 0.012 mass% to 0.035 mass% Ti, 0.0001 mass% to 0.03 mass% B, a Zn content of 0.25 mass% or less, a Zr content of 0.05 mass% or less, and the balance being Al and unavoidable impurities. The intensity of the diffraction peak of the AlFeMnSi phase in the X-ray diffraction pattern obtained by X-ray diffraction measurement of a cross section of this forged product 1 is defined as "Q 1 (cps), and the intensity of the diffraction peak of the (200) plane of the Al phase is "Q 2 " (cps), Q 1 / Q 2 The value is 8 x 10 -3 The present invention is characterized in that:
[0024] In this way, the content of each element is set within a predetermined range, and Q 1 / Q 2 The value is 8 x 10 -3 By satisfying the above condition, it is possible to provide an aluminum alloy forging having excellent mechanical properties at room temperature and in which recrystallized grains are unlikely to occur.
[0025] The method for manufacturing an aluminum alloy forging 1 according to the present embodiment involves carrying out a molten metal forming step, a casting step, a homogenizing heat treatment step, a forging step, a solution treatment step, a quenching treatment step, and an aging treatment step in this order to manufacture an aluminum alloy forging 1 as shown in Fig. 1, for example. Each step will be described below.
[0026] (Molten metal formation process) The molten metal forming step is a step in which raw materials are melted to obtain a molten aluminum alloy having a composition adjusted.
[0027] In this embodiment, a molten 6000 series aluminum alloy containing Cu: 0.15 mass% to 1.0 mass%, Mg: 0.6 mass% to 1.3 mass%, Si: 0.60 mass% to 1.45 mass%, Mn: 0.03 mass% to 1.0 mass%, Fe: 0.2 mass% to 0.4 mass%, Cr: 0.03 mass% to 0.4 mass%, Ti: 0.012 mass% to 0.035 mass%, B: 0.0001 mass% to 0.03 mass%, Zn content is 0.25 mass% or less, Zr content is 0.05 mass% or less, and the balance is Al and inevitable impurities is obtained (prepared). In this molten aluminum alloy, the Zn content may be 0 mass% (Zn not contained), and the Zr content may be 0 mass% (Zr not contained).
[0028] (Casting process) The casting step is a step of obtaining a casting by casting the aluminum alloy molten metal obtained in the molten metal forming step.
[0029] The continuous casting method for obtaining a cast product is not particularly limited, and various known continuous casting methods (vertical continuous casting method, horizontal continuous casting method, etc.) can be mentioned. As the vertical continuous casting method, a hot top casting method, etc. is used. Below, a brief description will be given of a case where an aluminum alloy continuous cast material is produced by a hot top casting method using a hot top casting device as an example of a continuous casting method (i.e., a case where an aluminum alloy continuous cast material is produced by continuously casting a molten aluminum alloy by the hot top casting method).
[0030] The hot top casting device is equipped with a mold, a molten metal receiving vessel (header), etc. The mold is cooled by cooling water that fills its interior. The receiving vessel is generally made of refractory material and is installed above the mold. The molten aluminum alloy in the receiving vessel is poured downward into the cooled mold, and is cooled and solidified at a predetermined cooling rate by the cooling water sprayed from the mold, and is further immersed in water (temperature: about 20°C) in a water tank where it solidifies completely. This produces long continuous cast material in the shape of a rod or the like.
[0031] (Homogenization heat treatment process) The homogenization heat treatment process is a process in which the cast material obtained in the casting process is subjected to homogenization heat treatment to homogenize microsegregations caused by solidification, precipitate supersaturated solid solution elements, and transform metastable phases into equilibrium phases.
[0032] In this embodiment, the casting obtained in the casting process is subjected to homogenization heat treatment by holding it at a temperature of 370° C. to 560° C. for 4 to 10 hours. By carrying out homogenization heat treatment in this temperature range, the ingot is homogenized sufficiently and solute atoms are sufficiently dissolved, so that sufficient strength required for the subsequent aging treatment can be obtained.
[0033] (Forging process) The forging step is a step in which the forging billet obtained after the homogenization heat treatment step is heated and pressed with a press to form it into a die.
[0034] In this embodiment, the ingot after the homogenization heat treatment is forged at a heating temperature of 450°C to 560°C to obtain a forged product (such as a suspension arm part for an automobile). At this time, the starting temperature for forging the forging material is 450°C to 560°C. If the starting temperature is less than 450°C, the deformation resistance becomes high and sufficient processing becomes impossible, and if it exceeds 560°C, defects such as forging cracks and eutectic melting are likely to occur.
[0035] (Solution treatment process) The solution treatment process is a process for relieving the strain introduced in the forging process and for dissolving the solute elements.
[0036] In this embodiment, the temperature of the forged product after the forging process is lowered to 20°C, and then heating begins once it has returned to room temperature. The temperature is increased at a rate of 5.0°C / min or higher throughout the entire temperature range from 20°C to 500°C, and the product is held at 530°C to 560°C for 0.3 to 3 hours to perform solution treatment.
[0037] When the heating rate is less than 5.0℃ / min, Mg 2 This is because coarse Si precipitates, and if the treatment temperature is less than 530°C, the solution treatment does not progress and high strength through aging precipitation cannot be achieved. On the other hand, if the treatment temperature exceeds 560°C, although the solid solution of the solute elements is further promoted, eutectic melting and recrystallization are more likely to occur.
[0038] (Hardening process) The quenching process is a heat treatment for forming a supersaturated solid solution by rapidly cooling the solid solution state obtained by the solution treatment process.
[0039] In this embodiment, the entire surface of the forged product is brought into contact with quenching water within 5 to 60 seconds after the solution treatment, and quenching is performed in the water tank for more than 5 minutes and up to 40 minutes.
[0040] (Aging treatment process) The aging treatment process is a heat treatment in which an aluminum alloy forged product is heated and held at a relatively low temperature to precipitate elements that are supersaturated in solid solution, thereby imparting an appropriate hardness.
[0041] In this embodiment, the forged product after the quenching process is heated at a temperature of 180°C to 220°C for 0.5 to 1.5 hours to undergo aging treatment. If the treatment temperature is less than 180°C or the treatment time is less than 0.5 hours, Mg, which improves the tensile strength, is not added. 2 When the treatment temperature exceeds 220°C, the Si precipitates cannot grow sufficiently and Mg 2 This is because the Si-based precipitates become too coarse to sufficiently improve the tensile strength.
[0042] As described above, in the manufacturing method of aluminum alloy forgings of the present invention, the content of each element is set within a prescribed range, and the processing conditions in each processing step are set within prescribed ranges, so that it is possible to manufacture aluminum alloy forgings that have even better mechanical properties at room temperature and are less susceptible to the generation of recrystallized grains.
[0043] Next, the composition of the "aluminum alloy" in the aluminum alloy forging and its manufacturing method according to the present invention will be described in detail below. The aluminum alloy contains 0.15% by mass to 1.0% by mass of Cu, 0.6% by mass to 1.3% by mass of Mg, 0.60% by mass to 1.45% by mass of Si, 0.03% by mass to 1.0% by mass of Mn, 0.2% by mass to 0.4% by mass of Fe, 0.03% by mass to 0.4% by mass of Cr, 0.012% by mass to 0.035% by mass of Ti, 0.0001% by mass to 0.03% by mass of B, 0.25% by mass or less of Zn, 0.05% by mass or less of Zr, and the balance being Al and unavoidable impurities.
[0044] Si coexists with Mg and becomes Mg 2 It forms Si-based precipitates and contributes to improving the strength of the final product. The amount of Si is smaller than the amount of Mg, which will be described later. 2 The Si content is preferably 0.60% by mass or more, since the strength of the final product after aging treatment is further increased by adding Si in excess of the amount that generates it. On the other hand, if the Si content exceeds 1.45% by mass, the grain boundary precipitation of Si increases, which makes the grain boundary embrittlement likely to occur, and not only reduces the plastic workability of the ingot and the toughness of the final product, but also there is a risk that the average grain size of the crystallized particles in the ingot will exceed a specified upper limit. Therefore, the Si content must be in the range of 0.60% to 1.45% by mass.
[0045] Mg coexists with Si to form Mg 2It forms Si-based precipitates and contributes to improving the strength of the final product. If the Mg content is less than 0.6 mass%, the effect of precipitation strengthening may be reduced. On the other hand, if it exceeds 1.3 mass%, not only will it reduce the plastic workability of the ingot and the toughness of the final product, but it may also cause the average grain size of the crystallized particles in the ingot to exceed a predetermined upper limit. Therefore, the Mg content must be in the range of 0.6 mass% to 1.3 mass%.
[0046] Cu is Mg 2 Increase the apparent supersaturation of Si-based precipitates and increase Mg 2 Increasing the amount of Si precipitation significantly promotes the age hardening of the final product. If the Cu content is less than 0.15 mass%, the Q phase (Al-Cu-Mg-Si), which is effective for precipitation strengthening, is difficult to form, resulting in a decrease in mechanical properties. On the other hand, if the Cu content exceeds 1.0 mass%, the forgeability of the ingot and the toughness of the final product are reduced, and there is a risk of a significant decrease in corrosion resistance. Therefore, the Cu content must be in the range of 0.15 mass% to 1.0 mass%.
[0047] Mn crystallizes as an AlMnSi phase, and Mn that does not crystallize precipitates and suppresses recrystallization. This effect of suppressing recrystallization makes the crystal grains fine even after plastic processing, and improves the toughness and corrosion resistance of the final product. If the Mn content is less than 0.03 mass%, the above-mentioned effects may be reduced. On the other hand, if it exceeds 1.0 mass%, giant intermetallic compounds may be generated, and the ingot structure of the present invention may not be satisfied. Therefore, the Mn content must be in the range of 0.03 mass% to 1.0 mass%.
[0048] Cr also crystallizes as an AlCrSi phase, and Cr that does not crystallize precipitates and suppresses recrystallization. This effect of suppressing recrystallization makes the crystal grains fine even after plastic processing, and improves the toughness and corrosion resistance of the final product. If the Cr content is less than 0.03 mass%, the above-mentioned effects may be reduced. On the other hand, if the Cr content exceeds 0.4 mass%, giant intermetallic compounds may be generated, and the ingot structure of the present invention may not be satisfied. Therefore, the Cr content must be in the range of 0.03 mass% to 0.4 mass%.
[0049] Fe combines with Al and Si to crystallize in the alloy, and prevents grain coarsening. If the Fe content is less than 0.2 mass%, the above effects may not be obtained. If the Fe content exceeds 0.4 mass%, coarse intermetallic compounds may be generated, and the plastic workability may deteriorate. Therefore, the Fe content must be 0.2 mass% to 0.4 mass%.
[0050] Zn is treated as an impurity, and if it exceeds 0.25 mass %, it accelerates the corrosion of aluminum itself and deteriorates the corrosion resistance, so the content must be 0.25 mass % or less.
[0051] Zr is treated as an impurity, and if it exceeds 0.05 mass%, the grain refining effect of the Al-Ti-B alloy is weakened, resulting in a decrease in the strength of the processed product after plastic working, so the content must be 0.05 mass% or less.
[0052] Ti is an alloying element effective in refining crystal grains, and also prevents the occurrence of ingot cracks in continuously cast rods. If the Ti content is less than 0.012% by mass, the refining effect is not obtained, while if it exceeds 0.035% by mass, coarse Ti compounds may crystallize, deteriorating toughness. Therefore, the Ti content must be in the range of 0.012% to 0.035% by mass.
[0053] Like Ti, B is also an element effective in refining crystal grains, and if its content is less than 0.0001 mass%, the effect is not obtained, while if its content exceeds 0.03 mass%, there is a risk of the toughness being deteriorated. Therefore, the B content must be in the range of 0.0001 mass% to 0.03 mass%. EXAMPLES
[0054] Next, specific examples of the present invention will be described, but the present invention is not particularly limited to these examples.
[0055] <Examples 1 to 12> A continuous cast material with a circular cross section and a diameter of 54 mm was produced from an aluminum alloy having the alloy composition shown in Table 1, and was subjected to homogenization heat treatment under the conditions shown in Table 1. The obtained cast material was forged under the conditions shown in Table 1 and plastically processed into the shape of an automobile suspension arm part shown in Figure 1.
[0056] Next, heating and solution treatment were performed under the conditions shown in Table 1, followed by quenching treatment as shown in Table 1, and then aging treatment to obtain aluminum alloy forgings 1.
[0057] <Comparative Examples 1 to 5> A continuous cast material with a circular cross section and a diameter of 54 mm was produced from an aluminum alloy having the alloy composition shown in Table 2, and was subjected to homogenization heat treatment under the conditions shown in Table 2. The obtained cast material was forged under the conditions shown in Table 2 and plastically processed into the shape of an automobile suspension arm part shown in Figure 1.
[0058] Next, heating and solution treatment were performed under the conditions shown in Table 2, followed by quenching treatment as shown in Table 2, and then aging treatment to obtain aluminum alloy forgings 1.
[0059] In addition, quenching begins when the entire forged product is immersed in water.
[0060] [Table 1]
[0061] [Table 2]
[0062] Each of the aluminum alloy forged products obtained as described above was evaluated according to the following evaluation methods.
[0063] <Method for evaluating strength at room temperature> Tensile test pieces having a gauge length of 25.4 mm and a parallel part diameter of 6.4 mm were taken from the obtained aluminum alloy forgings, and the tensile test pieces were subjected to a room temperature (25°C) tensile test to measure the yield strength and evaluate it based on the following criteria.
[0064] (Judgment criteria) "◎": Yield strength at room temperature is 360 MPa or more "○": Yield strength at room temperature is 340 MPa or more and less than 360 MPa "△": Yield strength at room temperature is 320MPa or more but less than 340MPa "X": The yield strength at room temperature is less than 320 MPa.
[0065] As is clear from Table 1, the aluminum alloy forgings of Examples 1 to 12 produced by the production method of the present invention were excellent in yield strength at room temperature.
[0066] In contrast, as shown in Table 2, the aluminum alloy forged products of Comparative Examples 1 to 5, which deviate from the range specified by the present invention, were inferior in yield strength at room temperature.
[0067] <Method for measuring the intensity of diffraction peaks of Al phase and AlFeMnSi phase in aluminum alloy forgings> X-ray diffraction measurements were performed on each aluminum alloy cast material and each aluminum alloy extrusion material using an X-ray diffractometer (SmartLab) manufactured by Rigaku Corporation. A plate-shaped piece measuring 10 mm x 10 mm x 2 mm thick was taken from the forged product and used as the X-ray diffraction measurement sample. In the X-ray diffraction pattern obtained by the X-ray diffraction measurement, the diffraction peak of the (200) plane of the Al phase was identified and the diffraction peak intensity of the (200) plane of the Al phase was obtained, and the diffraction peak of the AlFeMnSi phase was identified and the diffraction peak intensity of this AlFeMnSi phase was obtained. From these, the Q 1 / Q 2 The results are shown in Tables 1 and 2.
[0068] As shown in Table 1, in Examples 1 to 12, Q 1 / Q 2 The value is 8×10 -3 It can be seen that it is smaller.
[0069] In contrast, as shown in Table 2, in Comparative Examples 1 to 5, Q 1 / Q 2 The value is 8×10 -3 It can be seen that the above is the case. [Industrial Applicability]
[0070] The forged products obtained by the method for producing aluminum alloy forged products according to the present invention have excellent mechanical strength at room temperature and are therefore suitable for use, for example, as suspension parts such as suspension arm parts for automobiles, although they are not particularly limited to such applications. [Explanation of symbols]
[0071] 1: Aluminum alloy forgings
Claims
1. An aluminum alloy forging containing 0.15 mass% to 1.0 mass% Cu, 0.6 mass% to 1.3 mass% Mg, 1.20 mass% to 1.45 mass% Si, 0.03 mass% to 1.0 mass% Mn, 0.2 mass% to 0.4 mass% Fe, 0.03 mass% to 0.4 mass% Cr, 0.012 mass% to 0.035 mass% Ti, and 0.0001 mass% to 0.03 mass% B, with a Zn content of 0.25 mass% or less, a Zr content of 0.05 mass% or less, and the balance being Al and unavoidable impurities, The intensity of the diffraction peak of the AlFeMnSi phase in the X-ray diffraction pattern obtained by the X-ray diffraction measurement of the cross section of the forged product is defined as "Q 1 " (cps), and the intensity of the diffraction peak of the (200) plane of the Al phase is "Q 2 " (cps), Q 1 / Q 2 The aluminum alloy forging has a value of 8.2 × 10 -5 or less.
2. A method for producing an aluminum alloy forged product according to claim 1, a molten metal forming step for obtaining a molten metal; a casting step of obtaining a casting by casting the molten metal obtained in the molten metal forming step; a homogenization heat treatment step in which homogenization heat treatment is performed on the casting obtained in the casting step; A forging process for obtaining a forged product by forging the cast product after the homogenization heat treatment process; a solution treatment step of subjecting the forged product obtained in the forging step to a solution treatment; a quenching treatment step of quenching after the solution treatment step; and an aging treatment step of subjecting the forged product after the quenching treatment step to aging treatment.
3. An aluminum alloy forging containing, by mass, Cu: 0.15% to 1.0% by mass, Mg: 0.6% to 1.3% by mass, Si: 0.60% to 1.45% by mass, Mn: 0.03% to 1.0% by mass, Fe: 0.2% to 0.4% by mass, Cr: 0.03% to 0.4% by mass, Ti: 0.012% to 0.035% by mass, B: 0.0001% to 0.03% by mass, a Zn content of 0.25% or less, a Zr content of 0.05% or less, and the balance being Al and unavoidable impurities, A method for producing an aluminum alloy forging having a Q1 / Q2 value of 8.2×10-5 or less, wherein the intensity of the diffraction peak of the AlFeMnSi phase in an X-ray diffraction pattern obtained by X-ray diffraction measurement of the cross section of the forging is "Q1" (cps) and the intensity of the diffraction peak of the (200) plane of the Al phase is "Q2" (cps), a molten metal forming step for obtaining a molten metal; a casting step of obtaining a casting by casting the molten metal obtained in the molten metal forming step; a homogenization heat treatment step in which homogenization heat treatment is performed on the casting obtained in the casting step; A forging process for obtaining a forged product by forging the cast product after the homogenization heat treatment process; a solution treatment step of subjecting the forged product obtained in the forging step to a solution treatment; a quenching treatment step of quenching after the solution treatment step; and an aging treatment step for performing aging treatment on the forged product after the quenching treatment step. The homogenization heat treatment step is a homogenization heat treatment step in which the casting obtained in the casting step is held at a temperature of 370°C to 560°C for 4 hours to 10 hours, The forging process is a process of forging the casting after the homogenization heat treatment process at a heating temperature of 450°C to 560°C. The solution treatment step is a step of heating the forged product obtained in the forging step from 20°C to 500°C at a heating rate of 5.0°C / min or more, and then holding the product at 530°C to 560°C for 0.3 hours to 3 hours. In the quenching treatment step, the entire surface of the forged product is brought into contact with quenching water within 5 to 60 seconds after the solution treatment step, and quenching is performed in a water tank for more than 5 minutes but not exceeding 40 minutes. The method for manufacturing an aluminum alloy forged product is characterized in that the aging treatment step involves heating the forged product after the quenching treatment step at a temperature of 180°C to 220°C for 0.5 hours to 1.5 hours to perform aging treatment.
Citation Information
Patent Citations
Aluminum alloy forge piece as well as preparation method and application thereof
CN109136669A
Aluminum alloy for forging
JP1993059477A
Production of aluminum alloy for forging and forged product of aluminum alloy
JP1993247574A
Aluminum alloy cast member for forging
JP1994256880A
Plastic-worked article made from aluminum alloy, manufacturing method therefor, automotive parts, aging treatment furnace, and system for manufacturing plastic-worked article made from aluminum alloy
JP2007009273A